Present GPS velocity field along 1999 Izmit rupture zone: evidence for continuing afterslip 20 yr after the earthquake. Issue 3 (19th November 2020) - Özarpacı, Seda; Doğan, Uğur; Ergintav, Semih; Çakır, Ziyadin; Özdemir, Alpay; Floyd, Michael; Reilinger, Robert
SUMMARY: In order to better assess earthquake hazards, it is vital to have a better understanding of the spatial and temporal characteristics of fault creep that occur on ruptured faults during the period following major earthquakes. Towards this end, we use new far-field GPS velocities from continuous stations (extending ∼50–70 km from the fault) and updated near-fault GPS survey observations, with high temporal and spatial density, to constrain active deformation along the M w 7.4, 1999 Izmit, Turkey Earthquake fault. We interpret and model deformation as resulting from post-seismic afterslip on the coseismic fault. In the broadest sense, our results demonstrate that logarithmically decaying post-seismic afterslip continues at a significant level 20 yr following 1999 Earthquake. Elastic models indicate substantially shallower apparent locking depths at present than prior to the 1999 Earthquake, consistent with continuing afterslip on the coseismic fault at depth. High-density, near-fault GPS observations indicate shallow creep on the upper 1–2 km of the coseismic fault, with variable rates, the highest and most clearly defined of which reach ∼12 mm yr −1 (10–15 mm yr −1, 95 per cent c.i.) near the epicentre between 2014–2016. This amounts to ∼half the long-term slip deficit rate.